A bilayer thermal-electric camouflage device suitable for a wide range of natural materials. (1st April 2021) - Zhang, Xingwei; He, Xiao; Wu, Linzhi
Abstract: Thermal-electric camouflage device can hide an object from heat flux and DC current simultaneously. Due to the approximate solutions of the camouflage conditions, the currently proposed dual-physical camouflage devices are heavily dependent on materials, that is, they are only effective for some specific materials approximately. In order to expand the range of the applicable materials, a bilayer coat is introduced to achieve the accurate solutions of the camouflage equations, for there are two camouflage equations to solve two unknown quantities. Furthermore, a new type of effective medium method based on the theory of composites is introduced to further expand the range of the applicable materials. Therefore, a kind of thermal-electric camouflage device available to any natural materials is proposed and verified in this paper.